Wearable Device for Fall Detection Using 3-D Accelerometer - Nasiya, PM (International Journal of Computer Sciences and Engineering, 2018)
A fall detection device is needed to provide information to paramedics or family members when an elderly is falling. Helping for elderly falling can avoid fatal injuries or loss of life. In order for the falling device comfortably taken by the elderly, this proposed a wearable device that lightweight, using battery for power supply, and a low-energy consumption. proposed device consists of 3-dimensional accelerometer, a communication device and a microcontroller . The sensor meassures accelerations of body movements. Then, the microcontroller identifies position body and a falling from three-axis accelerations. proposed method, that has success detect 75% in fall forward and 95% in fall backward. The proposed device also has a 100% success in providing information on normal activities, such as: standing or sitting, supine, face down, left and right, while the success rate for the e-health device by cooking hack is 92%.